2021
DOI: 10.7759/cureus.15387
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Eustachian Valve Mimicking Inferior Rim of Atrial Septum Causing Iatrogenic Inferior Vena Cava Type Sinus Venosus Atrial Septal Defect

Abstract: The Eustachian valve is an embryologic remnant at the junction of the inferior vena cava (IVC) and right atrium (RA). While it typically does not have any pathologic significance, veno-arterial shunting can rarely occur in patients with prominent eustachian valves and atrial septal defects (ASD), causing cyanosis and hypoxemia despite normal pulmonary pressures. We present a case of a patient with iatrogenic residual sinus venosus IVC-type ASD secondary to a prominent Eustachian valve that was misinterpreted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They found that approximately 65% of patients had significant improvement in oxygen saturation after the closure procedure, with some patients even having complete resolution of their dyspnea and hypoxemia. Patients with no signs of improvement following PFO closure were identified to have a pulmonary cause underlying their hypoxia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that approximately 65% of patients had significant improvement in oxygen saturation after the closure procedure, with some patients even having complete resolution of their dyspnea and hypoxemia. Patients with no signs of improvement following PFO closure were identified to have a pulmonary cause underlying their hypoxia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predefined fluoroscopic end position in the aorta was at the level of the diaphragm with 2/3 of the balloon above the diaphragm and 1/3 below. The predefined fluoroscopic end position of the suprahepatic inferior vena cava balloon was at the level of the most cranially located hepatic vein, caudal to the right atrium and, when visible, the eustachian valve, ‘the valve of the inferior vena cava’ 26. Three persons performed all the procedures and measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The predefined fluoroscopic end position of the suprahepatic inferior vena cava balloon was at the level of the most cranially located hepatic vein, caudal to the right atrium and, when visible, the eustachian valve, ‘the valve of the inferior vena cava’. 26 Three persons performed all the procedures and measurements. One person measured the time, the second performed the ultrasound exam and the third positioned the endovascular balloons.…”
Section: Methodsmentioning
confidence: 99%